'Didi, are you Hindu?' Politics of Secularism in Women's Activism in India: Case-study of a grassroots women's organization in rural Uttar Pradesh*. (21st November 2012) - GOVINDA, RADHIKA
Abstract: In this paper I take the women's movement as the site for unpacking some of the strains and tensions involved in practical interpretations of secularism in present-day India. Several sources within and outside the movement point out that there has been a tendency to take the existence of secularism for granted, and that the supposedly secular idioms and symbols used for mobilizing women have been drawn from Hindu religio-cultural sources. Women from Dalit and religious minority communities have felt alienated by this. Hindu nationalists have cleverly appropriated these idioms and symbols to mobilize women as foot soldiers to further religious nationalism. Through a case-study of a grassroots women's NGO working in Uttar Pradesh, I seek to explore how women's organizations may be reshaping their agendas and activism to address this issue. Specifically, I will examine how and why the 2002 Gujarat riots affected the NGO, the ways in which it has started working on the issue of communal harmony and engaging with Muslims since the riots, and the challenges with which it has been confronted as a result of its efforts. In doing so, I will show how the complexities of NGO-based women's activism have become intertwined with the politics of secularism.